Scale Economies and the Volume of Trade - Harrigan, James (The Review of Economics and Statistics, 1994)
This paper offers a theoretical explanation of why previous attempts to statistically explain intraindustry trade have been unsuccessful and proposes an econometric approach that tests the implications of the monopolistic competition model for the volume of trade. Using disaggregated data on 1983 manufacturing trade within the OECD, the paper finds strong evidence that bilateral imports depend systematically on the exporting country's output and somewhat weaker evidence that the volume of trade is higher in sectors with larger scale economies. Copyright 1994 by MIT Press.